Ein Bild sagt mehr als tausend Worte:. (December 2013) - Wahl, Michael; Gnaser, Hubert; Kopnarski, Michael
<x xml:space="preserve">Abstract</x> A picture tells more than a thousand words: Applications of 3D atom probe tomography in thin‐film and nanoanalysis The characterization of structures currently used in thin film and nanotechnology constitutes an extreme challenge to the techniques of surface and materials analysis presently available, often going beyond their actual capabilities. In particular, their detection sensitivities and spatial resolution may not be sufficient to cope with the requirements posed by those technologies. The application of modern, commercial 3D atom probe tomographic (APT) instruments has considerably extended the range of analytical problems that can be tackled and solved. APT combines the quantitative and highly sensitive characterization of the chemical content of materials with a three‐dimensional registration of elemental distributions, achieving potentially atomic spatial resolution both laterally and in‐depth. While the first part of this contribution, published in the last issue, has presented the basic physical and instrumental principles of APT, this second part will discuss two selected applications from magnetic storage and silicon nanotechnology. They will serve to illustrate the new analytical capacities provided by atom probe tomography for the investigation of thin‐film and nano‐scale structures.